Patient simulator to drive diagnostic thinking process and deep learning - P. L., Or, P.; C.F, So, H.; C.L.C, Leung; J.W.Y, Chung, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
BackgroundThe aim of this study was to evaluate clinical reasoning of the diagnostic thinking process amongstudent nurses in pre-enrollment nursing programs in two different educational institutions usinga patient simulator.MethodThis study adopted a quasi-experimental design. Problem behavior graphs (PBGs) were drawnto reflect the participants’ clinical reasoning processes. Biggs’ Study Process Questionnaire(SPQ) was used to evaluate their study approaches into six sub-scales.ResultsForty-two subjects were randomly drawn from students of two pre-enrollment nursing programs:21 from a college and 21 from a hospital-based nursing school. Subjects from the college hadmore data driven strategy (53%) in the problem behavior graphs (PBGs). They used more surfacestrategy than subjects from the nursing school (47%).ConclusionsResults pinpoint data-driven strategy in nursing education helps to improve the current nursingeducation in Hong Kong. Only if the ability to master diagnostic thinking process from studentnurses ensures patient safety in clinical environments.